Target‐Specific Dermatological Adverse Event Reporting With T‐Cell–Engaging Bispecific Antibodies: A Pharmacovigilance Analysis of FAERS and Canada Vigilance, 2016–2026 - Saikat Mandal; Manideepa Maji; Arkadeep Dhali (Cancer Medicine, 2026)
ABSTRACT Background T‐cell–engaging bispecific antibodies are increasingly utilised in haematological malignancies and are beginning to be adopted in solid‐tumour treatment protocols. Cytokine release syndrome and neurotoxicity are well recognised, but target‐specific dermatological adverse event reporting patterns remain poorly defined. Methods We analysed 12,333,305 deduplicated FAERS reports from 2016Q1 to 2026Q1, including 23,386 reports exposed to ten T‐cell–engaging bispecific antibodies grouped by target: CD19, CD20, BCMA, GPRC5D and DLL3. A disease‐matched haematologic‐oncology comparator cohort contained 1,062,195 reports. Canada Vigilance provided a secondary directional comparison using 755,911 reports from 2016Q1 to 2025Q4 including 662 unique exposed reports. Outcomes were any cutaneous adverse event, broad severe cutaneous adverse reaction, and narrow Stevens‐Johnson syndrome/toxic epidermal necrolysis. Multivariable models adjusted for age, sex, cancer indication, polypharmacy and classical culprit drugs. Cox models assessed target‐specific timing. Results Among exposed FAERS reports, 1394 (5.96%) included any cutaneous adverse event, 61 (0.26%) broad severe cutaneous adverse reaction and 9 (0.04%) narrow Stevens‐Johnson syndrome/toxic epidermal necrolysis. After disease matching, no clear class‐level excess of severe cutaneous reaction reporting was observed. Talquetamab had the highest cutaneous reporting proportion (471/1822; 25.8%) and an elevated timing estimate (hazard ratio 1.34; 95% CI, 1.06–1.69), with enrichment for skin, hair, sweat‐gland and rash phenotypes. Tarlatamab showed an exploratory early‐onset pattern (hazard ratio 3.36; 95% CI, 1.68–6.72; median onset, 4 days), based on only eight reports with usable latency data. Canada Vigilance showed a similar direction of reporting for GPRC5D/any cutaneous adverse events. Conclusions T‐cell–engaging bispecific antibodies did not show clear class‐level excess in severe cutaneous adverse‐event reporting after disease matching. Talquetamab showed higher reporting of skin changes, hyperhidrosis, hair abnormalities and rash, whereas tarlatamab showed a possible early‐onset cutaneous reporting pattern based on a small number of reports with usable timing data. These findings support target‐ and timing‐aware dermatological monitoring and require prospective confirmation.